Determinants of Intention to Purchase a Controversial Halal Cosmetic: The Role of Perceived Expertise - Aisyah, Siti; Aji, Hendy Mustiko (UNISSULA, 2023)
This study investigates the link between perceived expertise, perceived risk, attitude, and purchase intention regarding a controversial halal cosmetic product. This study collected data from 128 Muslim participants who follow influencers discussing potential risks of a specific halal cosmetic brand on Instagram. A PLS-SEM approach was used to analyze the research model. This study revealed that perceived expertise and attitudes have a significant impact on the intention to purchase a controversial halal cosmetic. Interestingly, this study observed no significant connection between perceived risk and attitude or purchase intention. This suggests that when it comes to buying controversial halal cosmetics, consumers may not view perceived risk as a crucial factor. Instead, they seem to be more influenced by expert opinions. This study adds to the existing literature by exploring factors that influence the intention to purchase controversial halal cosmetics.